Pharmacological studies of anti-inflammatory, anti-nociceptive and anti-pyretic compounds found in chromatographic fractions of Anogeissus leiocarpa (DC). Guill. & Perr. leaves - Precious A. Idakwoji; Francis O. Atanu; Paul C. Nweje-Anyalowu; Theophilus B. Momoh; Wisdom O. Oniwon; Sara T. Elazab; Souty M.Z. Sharkawi; Rania M. Waheed; Amal Youssef; Gaber El-Saber Batiha (GarVal Editorial Ltda., 2022)
Context: The anti-nociceptive and anti-pyretic properties of the crude aqueous extract of Anogeissus leiocarpa (DC). Guill. & Perr. leaves have been reported. Aims: To investigate the anti-inflammatory, anti-nociceptive, and anti-pyretic properties of aqueous extract of A. leiocarpa leaves (AEAL) and its fractions to identify the bioactive compound(s). Methods: AEAL was fractionated successively and eluted in gradients of solvent mixture (n-hexane, ethylacetate, and methanol). Eluates, which showed similar TLC profiles were pooled to afford 5 fractions (F1-F5). AEAL and the fractions were subjected to phytochemical analysis and investigated for anti-inflammatory, anti-nociceptive, and anti-pyretic effects using carrageenan-induced paw edema and Brewer's yeast-induced pyrexia in rats, and acetic acid-induced writhing in mouse models, respectively. Results: Phytochemical analysis indicated presence of terpenoids, saponins, steroids, glycosides, flavonoids, tannins and alkaloids. At 200 mg/kg b.w, AEAL and F1-F5 recorded significant (p<0.05) improvements in paw edema, abdominal constrictions and pyrexia, which is comparable to the standard (ketoprofen or Aspirin), relative to the control groups, with F4 observed to be the most potent fraction. GC-MS analysis of F4 reveal the presence of hexadecenoic acid, 15-methyl-, methylester, 9-oxabicyclo (6.1.0) nonane, cis-, cholest-4-en-3-one, cholesterol and 3-diazo-1-methyl-1, 3-dihydro-indol-2-one. Conclusions: The results indicate that identified compounds, particularly 3-dihydro-indol-2-one, could be responsible for the anti-inflammatory, anti-nociceptive, and anti-pyretic properties of the extract.